Dimerization and Transactivation Domains as Candidates for Functional Modulation and Diversity of Sox9 - Geraldo, Marcos Tadeu [UNESP]; Valente, Guilherme Targino [UNESP]; Nakajima, Rafael Takahiro [UNESP]; Martins, Cesar [UNESP] (Public Library of Science (PLoS), 2016)
Sox9 plays an important role in a large variety of developmental pathways in vertebrates. It is composed of three domains: high-mobility group box (HMG box), dimerization (DIM) and transactivation (TAD). One of the main processes for regulation and variability of the pathways involving Sox9 is the self-gene expression regulation of Sox9. However, the subsequent roles of the Sox9 domains can also generate regulatory modulations. Studies have shown that TADs can bind to different types of proteins and its function seems to be influenced by DIM. Therefore, we hypothesized that both domains are directly associated and can be responsible for the functional variability of Sox9. We applied a method based on a broad phylogenetic context, using sequences of the HMG box domain, to ensure the homology of all the Sox9 copies used herein. The data obtained included 4,921 sequences relative to 657 metazoan species. Based on coevolutionary and selective pressure analyses of the Sox9 sequences, we observed coevolutions involving DIM and TADs. These data, along with the experimental data from literature, indicate a functional relationship between these domains. Moreover, DIM and TADs may be responsible for the functional plasticity of Sox9 because they are more tolerant for molecular changes (higher Ka/Ks ratio than the HMG box domain). This tolerance could allow a differential regulation of target genes or promote novel targets during transcriptional activation. In conclusion, we suggest that DIM and TADs functional association may regulate differentially the target genes or even promote novel targets during transcription activation mediated by Sox9 paralogs, contributing to the subfunctionalization of Sox9a and Sox9b in teleosts.